Organizational learning: a capacity of the research groups at the public university - Conde Cardona, Yenni; Correa Correa, Zamanda; Delgado Hurtado, Carolina (Cuadernos de Administración, 2010)
One of the main concerns of the universities that have economical resources for research, is related to the way how the processes can be evaluated and carried out by the research groups in terms of their inputs, outputs, outcomes and impacts. The measurement systems for research and development are focused on the results achieved by groups in terms of production regardless of the processes, outcomes and impacts achieved, so that, in general, society does not value the real scope and significance of the research function. This work considers learning as one of the important outcomes of the investigative processes mentioned and seeks to determine how it occurs within the research groups of a public university in each of three levels: individual, group and organizational, with a sample formed by 111 members of research groups recognized by Colciencias ,using a descriptive cross-sectional method. For this purpose there was adapted and applied an instrument developed by Castaneda and Fernandez (2006), which identifies how learning occurs in each of these three levels, and in-depth interviews were conducted. The information was analysed with the statistical package SPSS 11.5 V. The results obtained allowed the determination that the learning in this University occurs in the three levels considered, however, organizational learning that occurs in the research groups is not optimal, the knowledge of the researchers is not used to improve the processes of the University or to generate new products and services. In the same way the learning of the university in the face of the pressures from the environment is casual. Accordingly, the University should consider improving it’s capacity of response towards the environment, with elements that it has through the knowledge that the researchers apply.